1983
DOI: 10.1007/bf00284464
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of glucose transport in hearts of genetically obese (fa/fa) Rats

Abstract: Summary. Overall D-glucose metabolism and 3-0-methylglucose transport were measured in the perfused heart preparation of lean and genetically obese (fa/fa) rats. Absolute values of basal and insulin-stimulated glucose metabolism were decreased in hearts of 15-week-old obese rats when compared to lean age-matched controls. Basal and maximally stimulated (i. e., by the combined addition of insulin and increasing perfusion pressure) 3-0-methylglucose transport was normal in hearts from young obese rats (5-week-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 25 publications
2
23
1
Order By: Relevance
“…1). These findings corroborate those of others made in other muscle types [4][5][6] and suggest that, although the heart is not representative of the muscle mass, it may undergo -upon the occurrence of insulin resistance -changes that are analogous to those seen in other muscles. This strengthens the observations made during the present study, with regard to the state of the glucose transporters as assessed by the cytochalasin B-binding assay.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…1). These findings corroborate those of others made in other muscle types [4][5][6] and suggest that, although the heart is not representative of the muscle mass, it may undergo -upon the occurrence of insulin resistance -changes that are analogous to those seen in other muscles. This strengthens the observations made during the present study, with regard to the state of the glucose transporters as assessed by the cytochalasin B-binding assay.…”
Section: Discussionsupporting
confidence: 89%
“…With regard to glucose uptake, it has been shown that basal, as well as insulin-stimulated glucose uptake, was decreased in most obesity syndromes studied [2,[4][5][6]. As is now well established in adipocytes [8,9] and also described in muscle [10], glucose transporting molecules (glucose transporters) are present both in the plasma and in some intracellular (microsomal) membranes.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, work-induced hypertrophy was able to compensate for decreased insulin responsiveness observed in GTG-obese muscles. Additive effects of insulin and work induced by pressure were also observed in perfused hearts from obese Zucker rats [29]. The mechanisms of such effects of exercise are unknown.…”
Section: Discussionmentioning
confidence: 98%
“…Fhe genetically obese OCa/fa) Zucker rat is a well-documented animal model for insulin resistance in skeletal [1,2] and cardiac m~tscle [3,4]. It has been suggested that a defect of the glucose ur take itself may contribute besides other defects to this insulin re,4stance [5,6].…”
Section: Introductionmentioning
confidence: 99%